Encontro Estadual dos Grupos Pet do Rio Grande do Sul (2.:2022, Bagé, RS) : caderno de resumos do II PetChê, Bagé,21 a 28 de maio de 2022 - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The II PETchê – State Meeting of PET Groups (Tutorial Education Program) of Rio Grande do Sul, organized by the PET groups of the Federal University of Pampa (Unipampa), took place on May 21 and 28, 2022, in remote mode. oriented under the theme “Borders that do not divide”, the event provided opportunities for PETs groups in the state to a space for debate and reflection on what brings us together as groups formed in the diversity and what makes us transforming agents in the region where we operate. The proposal of event was based on confronting borders in their most varied meanings, whether in the field of ideologies, cultures, genres, beliefs, as well as practices professionals. In addition, the event dealt with the training of professionals and citizens socially responsible and engaged in their community. Event II PETchê occurred after two years of pandemic, demonstrating the resistance of the PETs groups to foment the program activities. This book of abstracts brings together the works presented at the II PETchê. The event featured works by PET groups from the Federal University of Fronteira Sul, Federal University of Pelotas, Federal University of Rio Grande do Sul, Federal University of Santa Maria and the institution that hosted the event, the Federal University of Pampa. There was eighteen simple abstracts submitted, and the works presented in the online communication, and the quality of the work is attested by doctors and graduate students who evaluated them.
State Meeting of Pet Groups in Rio Grande do Sul (2.:2022, Bagé, RS): II PetChê abstract notebook, Bagé, May 21 to 28, 2022
Keywords: Educação; Ensino; Programa de educação tutorial; Teaching; Education; Programa de educação tutorial; CNPQ::CIENCIAS HUMANAS